Tortilla wrap dari tepung kacang hijau dengan isian ikan patin sebagai makanan selingan untuk ibu hamil - Dessita Qurniawati; Nani Ratnaningsih; Badraningsih Lastariwati (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
To prevent anemia in pregnant women, it is necessary to develop food products that are sources of nutrients, for example from mung beans. Mung beans can be processed into snacks such as tortilla wrap mung beans. This study aims to determine the recipe, level of preference, and nutritional content of tortilla wrap mung beans with catfish filling. This type of research uses RD (Research and Development) with a 4D design (Define, Design, Development and Disseminate). The preference test was carried out by 100 panelists of pregnant women and the proximate test on innovative products. Data analysis used descriptive statistics. The Tortilla Wrap Mung Beans recipe uses 30% substitution of mung bean flour from the total wheat flour. Overall, the level of preference for tortilla wrap mung beans has an average of 3.46 or preferred. The nutritional content of tortillawrap mung beans per serving (100 g) consists of energy 275.8 kcal, protein 11.49 g, fat 9.01 g, carbohydrates 42.26 g. Tortilla wrap mung beans is categorized as an iron source snack because the iron content is 15.75 mg per 100 g of product. Therefore, tortilla wrap mung beans with catfish filling can be recommended as an alternative snack source of iron for pregnant women.